On-surface Synthesis of a Chiral Graphene Nanoribbon with Mixed Edge Structure - Keerthi, Ashok; Sanchez-Sanchez, Carlos; Deniz, Okan; Ruffieux, Pascal; Schollmeyer, Dieter; Feng, Xinliang; Narita, Akimitsu; Fasel, Roman; Muellen, Klaus (Chemistry - An Asian Journal, 2020)
Chiral graphene nanoribbons represent an important class of graphene nanomaterials with varying combinations of armchair and zigzag edges conferring them unique structure-dependent electronic properties. Here, we describe the on-surface synthesis of an unprecedented cove-edge chiral GNR with a benzo-fused backbone on a Au(111) surface using 2,6-dibromo-1,5-diphenylnaphthalene as precursor. The initial precursor self-assembly and the formation of the chiral GNRs upon annealing are revealed, along with a relatively small electronic bandgap of approximately 1.6 eV, by scanning tunnelling microscopy and spectroscopy.
CRIS-Team Scopus Importer:2023-03-20
Keywords: chiral edge; graphene nanoribbon; on-surface synthesis; polycyclic aromatic hydrocarbon; scanning tunneling microscopy and spectroscopy